Lighting Systems of Khudoyorkhan Palace and Their Importance Today - Zakirova Gulnozaxon Maxammadjon qizi; Turgunboyev Azizbek Abdubannob o’g’li (Genius Journals, 2022)
In the 19th century, Khudoyorkhan Orda, a huge palace, had a system of baladiya, or communal services, adapted to the capabilities of the time and local conditions. However, this system is not currently in use and is one of the problems that will cause the building to lose its historicity.
Keywords: Hudoyorkhan; horde; palace; ballad